Impact of albumin-to-alkaline phosphatase ratio in gastric cancer patients treated with adjuvant chemoradiation - ALKIŞ, HİLAL (My University, 2023)
Background: Albumin-to-alkaline phosphatase ratio (AAPR) function as a prognostic indicator which is found to be decreased in several malignancies. In our study, we aimed to evaluate the association between clinicopathological features and pretreatment AAPR in gastric cancer patients received adjuvant chemoradiation. Methods: A total of 118 patients diagnosed with gastric cancer who underwent surgery and received adjuvant chemoradiation at the Department of Radiation Oncology between July 2013 and June 2023 were included in the study. Patients' clinicopathological features and albumin and alkaline phosphatase values at the time of diagnosis were recorded. Patients who received neoadjuvant chemo/radiotherapy were not included. Chemoradiation was administered with a dose of 45-50.4 Gy radiation with concurrent 5- fluorouracil/capecitabine. Descriptive statistics were used to examine the baseline characteristics of gastric cancer patients such as age, sex, histology (adenocarcinoma and non-adenocarcinoma), tumor, and nodal stage, grade, tumor location, lymphovascular invasion, and perineural invasion. Independent t-test was used for two variables, and one-way analysis of variance (ANOVA) test was used for more than two variables to analyze the relationship between AAPR and clinicopathological properties. Results: Median age was 59 (23-85) years. AAPR was found to be significantly decreased in patients with the histopathology of adenocarcinoma (P=0.04) (Table). However, there was not a statistically significant change in AAPR in terms of tumor/nodal stage, age, sex, perineural/lymphovascular invasion, and grade status. Conclusions: AAPR at the time of diagnosis in gastric cancer patients has a relationship with the histopathology of gastric cancer. However, further studies with larger study population are needed.
Keywords: Albumin-to-alkaline phosphatase ratio; gastric cancer; histopathology